2013
DOI: 10.1021/am403634u
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Bi2Te3-Based Topological Insulator Film Magnetic Field Detector

Abstract: Topological insulators with the nanoscaled metallic surface state (3-5 nm) are actually of typical functional nanostructures. Significant efforts have been devoted to study new families of topological insulators and identifications of topological surface state, as well as fundamental physics issues relating to spin-polarized surface electronic states in the past few years. However, transport investigations that can provide direct experimental evidence for potentially practical applications of topological insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The presence of unique topological quantum states is confined by spin orbit interaction and time reversal symmetry, which prevents backscattering from impurities and defects [1][2][3][4][5][6][7][8][9][10][11][12]. In TIs the electrons are localized in the bulk but delocalized at the edges [13]. Furthermore, TIs behaves as excellent thermoelectric (TE) materials due to the presence of analogous material features such as heavy elements and narrow band gaps [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of unique topological quantum states is confined by spin orbit interaction and time reversal symmetry, which prevents backscattering from impurities and defects [1][2][3][4][5][6][7][8][9][10][11][12]. In TIs the electrons are localized in the bulk but delocalized at the edges [13]. Furthermore, TIs behaves as excellent thermoelectric (TE) materials due to the presence of analogous material features such as heavy elements and narrow band gaps [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In TIs the electrons are localized in the bulk but delocalized at the edges [13]. Furthermore, TIs behaves as excellent thermoelectric (TE) materials due to the presence of analogous material features such as heavy elements and narrow band gaps [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, there have not been any investigations of the interaction between light and polycrystalline TIs. Yet, high-quality polycrystalline TI Bi 2 (Te, Se) 3 thin films have been prepared through pulsed-laser deposition (PLD)161718, and several detection experiments have confirmed that polycrystalline TI films provide an attractive material platform for exploring the nature and practical application of TIs19202122.…”
mentioning
confidence: 99%
“…The interior of a topological insulator (TI) resembles that of a conventional insulator; however, the surface state is conductive. [1][2][3][4][5][6][7][8][9][10][11][12][13] Conning electrons to the surface state induces novel behaviour. For example, the momentum and spin of electrons in TIs are constrained to be perpendicular, due to strong spin-orbit interaction.…”
Section: Introductionmentioning
confidence: 99%